Perilaku Pemangku Kepentingan (Stakeholder) Industri Genteng Dalam Pengelolaan Lingkungan di Kecamatan Moyudan dan Kecamatan Godean, Kabupaten Sleman, Yogyakarta - , Dian Rianti Mayasari ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Roof tile is an industry requiring raw material exploited directly from nature. The natural resource exploitation must cause environmental change such as abiotic, biotic and cultural. Roof tile industry has involve many stakeholders including main, primary, and secondary stakeholder. This research was intended to (1) explore roof tile industry history and its current condition, (2) explain motivation of land owner to sell their land for being mined, (3) explain environment management behavior every stakeholder do, and (4) explain relationship among stakeholder (stakeholder mapping). Research method used was case study method with survey and direct observation in field. In case study method, data obtained is not based on amount of sample but is focused on variety of informant. This research was conducted in some locations related directly to existence of roof tile, that is, Sidoluhur village in Godean district (roof tile industry), Pare subvillage, Sidoluhur village in Godean district (mining location) and Seteran, Donon, Joton, Pakelan subvillages in Sumberarum villages in Moyudan district (mining location). Descriptive qualitative analysis was done using analytical unit of individual and group of each stakeholder. Based on the results, roof tile industry is estimated begin in 1930s. However, at that time the business produced only roof tile for their needs. Roof tile industry that was run for economic business emerged around 1960s. Today, roof tile industry underwent growth difficulty. The difficulty is due to scarce clay, increased fuel price, and weather/climate uncertainty. In meeting roof tile industry need, some stakeholders such as land owner and clay supplier are required. Motivation of land owner to sell their soil is to make the land smooth and can be used for other usage. Environment management was done by all related stakeholders based on planning, usage, controlling, maintenance, monitoring, and law enforcement. Stakeholders have various role and interest that is explained with stakeholder mapping. Based on stakeholder mapping, relationship between stakeholders can be seen through matching and conflict matrix.